Anti-High-Density Lipoprotein Antibodies and Antioxidant Dysfunction in Immune-Driven Diseases - Rodríguez-Carrio, Javier; Mozo, Lourdes; López, Patricia; Nikiphorou, Elena; Suárez, Ana (Frontiers in Medicine, 2018)
Introduction Impaired high-density lipoprotein (HDL) levels and antioxidant functionality of HDL, mainly attributed to a decreased paraoxonase-1 (PON1) functionality, have been described in autoimmune conditions. In this setting, a role for humoral response in cardiovascular disease is emerging. This study evaluates the role of immunoglobulin G (IgG) antibodies against HDL and disease-related autoantibodies on HDL dysfunction in immune-driven diseases. Methods Serum IgG anti-HDL antibodies, PON1 activity, and total antioxidant capacity (TAC) were quantified in 381 patients with different immune-driven diseases [18 mixed connective tissue disease (MCTD), 35 primary Sjögren syndrome (pSS), 38 systemic sclerosis (SSc), 33 ANCA-associated vasculitis (AAV), 60 diabetes mellitus 1, 29 autoimmune B12 deficiency/pernicious anemia, 29 primary biliary cirrhosis, 46 IBD/Crohn, 54 IBD/UC, and 39 celiac disease (CD)] and 138 healthy controls. Results IgG anti-HDL antibodies were increased in MCTD, pSS, AAV, and inflammatory bowel disease (IBD) [Crohn and ulcerative colitis (UC)], even after correcting for total IgG levels, but not in organ-specific autoimmune diseases. Anti-HDL antibodies were negatively associated with PON1 activity in MCTD (r = −0.767, p < 0.001) and AAV (r = −0.478, p = 0.005), whereas both anti-HDL and anti-neutrophil cytoplasm antibod levels were related to an impaired PON1 activity and TAC in IBD/UC. In SSc, anti-centromere antibodies correlated PON1 activity. anti-Saccharomyces cerevisiae antibodies levels were negatively associated with PON1 activity (r = −0.257, p = 0.012) and PON1/TAC ratio (r = −0.261, p = 0.009) in IBD/Crohn. HDL dysfunction in CD was only related to anti-transglutaminase levels. Conclusion IgG anti-HDL antibodies and HDL dysfunction are common hallmarks of systemic autoimmunity. Anti-HDL and disease-related autoantibodies account for the HDL antioxidant dysfunction in immune-driven conditions, mainly in systemic autoimmune disorders.